VD_FINDINFO HC / 2015 / 849 vom 28. September 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, DIVORCE, MODIFICATION DES CIRCONSTANCES, ÉCOLAGE, OBLIGATION D'ENTRETIEN | 163 CC, 176 al. 1 ch. 1 CC, 179 al. 1 CC, 276 al. 1 CPC (CH)